2022
DOI: 10.1007/978-3-031-11371-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Transforming a Highly Tactile Entrepreneurship Course “Ideas to Innovation” to an Entirely Online Delivery Model: Lessons for Theory and Practice

Abstract: Recent changes in education due to COVID-19 required a shift from classroom to online delivery. This chapter illustrates how a highly complex training program, Ideas to Innovation (i2i), responded to this challenge. i2i is based on experiential learning including a variety of activities carried out both in large and small groups with the intention to raise delegates’ entrepreneurial self-efficacy. In this case study, we illustrate the process by which the program was delivered online for the first time since i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…The course which is the basis of this case study started in the winter term of 2020 at Hochschule Munich University of Applied Sciences, when Verena Kaiser and Bettina Maisch held a joint online entrepreneurship course on the topic of Green Tech, Agriculture, and Nutrition for students of their respective faculties of business administration and mechatronics. The course went well given the fact that Vaiciukynaite et al (2023) highlighted that COVID-19 infused challenges to entrepreneurial education that are more significant than in other business domains because entrepreneurial education is based on experiential education.…”
Section: Initial Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The course which is the basis of this case study started in the winter term of 2020 at Hochschule Munich University of Applied Sciences, when Verena Kaiser and Bettina Maisch held a joint online entrepreneurship course on the topic of Green Tech, Agriculture, and Nutrition for students of their respective faculties of business administration and mechatronics. The course went well given the fact that Vaiciukynaite et al (2023) highlighted that COVID-19 infused challenges to entrepreneurial education that are more significant than in other business domains because entrepreneurial education is based on experiential education.…”
Section: Initial Setupmentioning
confidence: 99%
“…This onsite week will be enriched with two preparatory online meetings plus sessions on intercultural management upfront, as well as the flipped classroom elements. Vaiciukynaite et al (2023) found that digital interaction and collaboration among participants and facilitators on various platforms promoted the development of an entrepreneurial mindset, therefore some online elements will be kept. Startup founders will be invited on each lecture day for short presentations of their companies and challenges.…”
Section: Enhanced Team Dynamics Through Consistent Gradingmentioning
confidence: 99%